EFEKTIFITAS INOKULASI ACTINOMYCETES DAN VAM DALAM MENGENDALIKAN PENYAKIT REBAH SEMAI (Sclerotium rolfsii ) PADA TIGA VARIETAS KEDELAI PADA MUSIM KEMARAU - Gusnawaty, HS (Jurnal Agroteknos, 2011)
ABSTRACT The aim of the research was to know the effectiveness of actinomycetes and VAM inoculations in preventing the occurrence of infection of Sclerotium rolfsii on soybean at dry season.  This  research  was  conducted  at  the  Phytophatology Laboratory,  Mycology  sub- Laboratory of the Plant Protection Faculty of Agriculture, University of Brawijaya, and in the trial plantation of Balai Benih Induk Palawija, Lawang, Malang subdistrict.   This research used the Random Group Design (RGD) which consisted of two factors, namely (1) variety factor consisted of  Ratai, Kaba and  Burangrang; (2)  inoculum factor, that  were  without actinomycetes and VAM inoculation, inoculation with actinomycetes, inoculation with VAM, combined inoculation of actinomycetes and VAM. The research result showed that the combined inoculation of actinomycetes and VAM could control the level of attack in three soybean varieties with the highest control effectiveness. Keywords: Actinomycetes, VAM, soybean, Sclerotium rolfsii